Thickness of Buccal Bone at Various Sites of the Mandible and Its Clinical Significance in MonocorticalScrews Placement Using Multi-Slice Computed Tomography - Hawraa N Atallah; Lamia H Al-Nakib (College of Dentistry/ University of Baghdad, 2015)
Background:Open reduction and internal fixation (ORIF) of using miniplates and screws is the treatment of choice of mandibular fractures. It is important to know both: the region where the bone providesafirm anchorage, andthe topography of the dental apices and inferior alveolar nerve to avoiddamaging them when inserting the screw. The aim of this study is to determine the thickness of buccal cortical plate and that of buccal bone at the parasymphysis and mandibular body, thereby determining the area that provide afirm anchorage and the maximum length of mono-cortical screws that can be safely placed in these regions without injuring the tooth roots or mandibular nerve. Materials and Methods:The sample of the present study was 110 Iraqi subjects (77 males & 33 females) aged (18-35) years old who admitted to Computed Tomography scan unit in AL-Sadr Teaching Hospital in Al-Najaf city to get Computed Tomographic examination of facial bones. The conventional sections of CT (axial, coronal) used to do the measurements and dental planning analysis also used. The thickness of buccal cortical plate and the thickness of buccal bone were measured at the level of root apex of (canine, first premolar, second premolar) and at the level ofroot apex and inferior alveolar canal in mesial and distal root of first and second molar. Results:There was no statistical significant difference in buccal cortical plate and buccal bone thickness between age and gender at most measured sites. Using of 4mm screw is safe in distal root region of 2nd molar at the level of apex and that of inferior alveolar canal for both males and females. Moving slightly forward in position to the mesial root of 2nd molar 1mm will be lost from safety margin, while making only the 3mm screw is safe. For the remaining anterior positions only the minimum screw length of 2 mm is safe. Conclusions:Thickness of buccal cortical plate and buccal bone in various sites could be measured precisely using Multislice Computed tomography which can guide surgeons in selecting the proper screw length without causing injury to tooth apex or inferior alveolar nerve.